Poverty knowledge : social science, social policy, and the poor in twentieth-century U.S. history - O'Connor, Alice, 1958- (Politics and society in twentieth-century America., 2001)
Progressive-era "poverty warriors" cast poverty in America as a problem of unemployment, low wages, labor exploitation, and political disfranchisement. In the 1990s, policy specialists made "dependency" the issue and crafted incentives to get people off welfare. Poverty Knowledge gives the first comprehensive historical account of the thinking behind these very different views of "the poverty problem," in a century-spanning inquiry into the politics, institutions, ideologies, and social science that shaped poverty research and policy. Alice O'Connor chronicles a transformation in the study of poverty, from a reform-minded inquiry into the political economy of industrial capitalism to a detached, highly technical analysis of the demographic and behavioral characteristics of the poor. Along the way, she uncovers the origins of several controversial concepts, including the "culture of poverty" and the "underclass." She shows how such notions emerged not only from trends within the social sciences, but from the central preoccupations of twentieth-century American liberalism: economic growth, the Cold War against communism, the changing fortunes of the welfare state, and the enduring racial divide